PENGARUH SALES PROMOTION DAN ONLINE CUSTOMER REVIEW TERHADAP KEPUTUSAN PEMBELIAN DI MARKETPLACE SHOPEE - Rr. Adira Mafaza; Siti Aminah (Jurnal Pendidikan Ekonomi (JURKAMI), 2022)
The rapid development of technology and information in the digital era triggers changes in people's lives. This is inseparable from the influence of increasing internet use and encouraging the rapid growth of the marketplace so that the marketplace is required to create efficient shopping facilities so that consumers are encouraged to make purchasing decisions. The purpose of this study was to determine the effect of Sales Promotion and Online customer review on purchasing decisions. The sampling method used is accidental sampling, namely the technique of determining the sample based on chance, namely prospective respondents who coincidentally meet the researcher can be used as research samples. The analysis technique uses Partial Least Square (PLS). The result of the research is that Sales Promotion contributes to the Purchase Decision. The higher the Sales Promotion offered by Shopee, the level of consumer purchasing decisions will increase. Meanwhile, Online customer reviews contribute to Purchase Decisions in the Shopee marketplace because the better the Online customer reviews provided, the higher the level of Consumer Purchase Decisions in the Shopee marketplace